1993
DOI: 10.1109/26.223779
|View full text |Cite
|
Sign up to set email alerts
|

Extremal properties of likelihood-ratio quantizers

Abstract: Let there be M hypotheses H 1 ,... , HM, and let Y be a random variable, taking values in a set y, with different probability distribution under each hypothesis. A quantizer -': Y-+ {1,..., D} is applied to form a quantized random variable 7(Y). We characterize the extreme points of the set of possible probability distributions of -(Y), as 7y ranges over all quantizers. We then establish optimality properties of likelihood-ratio quantizers for a very broad class of quantization problems, including problems inv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
118
0

Year Published

2003
2003
2013
2013

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 107 publications
(119 citation statements)
references
References 20 publications
1
118
0
Order By: Relevance
“…The network aims to minimize the probability of error or some other cost function at the fusion center, by choosing optimal transmission functions and fusion rules. Various properties and variants of the decentralized detection problem in a parallel configuration have been extensively studied over the last twenty-five years; examples include the following: [4][5][6][7][8] study the properties of optimal fusion rules and quantizers at sensor nodes; [9] shows the existence of optimal strategies, and proves that likelihood ratio quantizers are optimal for a large class of problems including the decentralized detection problem; and [10][11][12][13][14] consider constrained decentralized detection. The reader is referred to [15,16] for a survey of the work done in this area.…”
Section: Introductionmentioning
confidence: 99%
“…The network aims to minimize the probability of error or some other cost function at the fusion center, by choosing optimal transmission functions and fusion rules. Various properties and variants of the decentralized detection problem in a parallel configuration have been extensively studied over the last twenty-five years; examples include the following: [4][5][6][7][8] study the properties of optimal fusion rules and quantizers at sensor nodes; [9] shows the existence of optimal strategies, and proves that likelihood ratio quantizers are optimal for a large class of problems including the decentralized detection problem; and [10][11][12][13][14] consider constrained decentralized detection. The reader is referred to [15,16] for a survey of the work done in this area.…”
Section: Introductionmentioning
confidence: 99%
“…, N : Q a = X N j=1 Q j . As previously mentioned, it has been proved in [9] that Q j is a compact set, and thus any cost function that is a continuous function on Q j will attain a minimum. In a parallel configuration with multiple sensors and a fusion center, if the sensor observations are independent given each hypothesis, it has also been shown that there exists an optimal solution over the set Q a [9].…”
Section: A Backgroundmentioning
confidence: 93%
“…, D − 1}, each sensor can be considered as a quantizer. As mentioned in the Introduction, [9] characterizes these quantizers based on the set of marginal distributions of the messages given each hypothesis. Following [9], let…”
Section: A Backgroundmentioning
confidence: 99%
See 2 more Smart Citations